Cytogenetic and hematological study for some Iraqi women suffer from abortion - Abbas, Rafal N. (Iraqi Journal of Cancer and Medical Genetics, 2017)
Comet assay (Single cell electrophoresis assay ,SCGE) is a very sensitive method to determine DNA damage caused by exposure to mutagenic , carcinogenic and environmental agents that affect women infertility. This study was aimed to assess possible genomic instability in women with recurrent spontaneous abortion (RSA). Fifteen blood samples were collected from women complaining with RSA and 5 normal fertile females, who had at least one or more child. The results showed that patients female with RSA had a significant higher DNA damage than in the control group.